An Assessment of Pig Feed Diversity amongst Smallholder Pig Farmers in Northern Uganda - Okello, Daniel Micheal; Odongo, Walter; Aliro, Tony; Ndyomugyenyi, Elly (Cogent Food & Agriculture, 2021)
Pig production has a high potential for increasing household incomes of both rural and urban smallholder farmers. However, this opportunity is constrained by the high cost of feeds and its scarcity. As such, farmers usually feed pigs on multiple feed resources within their reach. Although the diversity of pig feeds is important in overcoming the challenges, there is limited information on how this can be achieved, and the factors influencing it. Using a cross-section of 240 pig farming households, this study assessed how socio-demographic, technical and institutional factors influenced household pig feed diversity. Statistical analysis was performed at p < 0.1, p < 0.05 and p < 0.01), respectively. Results showed that marital status (p = 0.012), household size (p = 0.085), number of crop (p = 0.008) and other livestock enterprises (p = 0.055), ownership of mobile phone (p = 0.091), buying feeds (p = 0.005), and use of radio (p = 0.032) and friend as sources (p = 0.002) of agricultural information had a positive significant influence on household pig feed diversity. Additionally, age (p = 0.042), land size owned (p = 0.085) and breed [rearing local (p = 0.009) and crosses (p = 0.000) as opposed to exotic breeds] had a negative significant influence on household pig feed diversity. The study recommends that focus should be placed on improving access to farm inputs, agricultural and market information for smallholder pig farmers so as to improve pig feed diversity and subsequently enhance production and productivity. Radio and mobile phone technologies are opportunities that can support information sharing.
Keywords: Smallholder pig production; feed resources; diversity; Uganda